Estimation of the Bandwidth of the Communication Channel of 5G Networks Based on Small Cells - Tsopa, O.; Dudka, O.; Merzlikin, A.; Ruzhentsev, N. (My University, 2021)
The article is devoted to the problem of using 5G millimeter waves band (MM WB) in wireless communication systems of the next generation. The aim of the work is to clarify the calculation methods and estimate the availability parameters and performance of communication channels in the millimeter wavelength band when deploying 5G communication network segments in various climatic zones of Ukraine.
Keywords: millimeter wave propagation; 5G; small cells; mobile communication; rain attenuation; IEEE 802.11ad